New Technologies With Increased Precision Improve Understanding of Endothelial Cell Heterogeneity in Cardiovascular Health and Disease - Dawson, Ashley; Wang, Yidan; Li, Yanming; LeMaire, Scott A.; Shen, Ying H. (Frontiers in Cell and Developmental Biology, 2021)
Endothelial cells (ECs) are vital for blood vessel integrity and have roles in maintaining normal vascular function, healing after injury, and vascular dysfunction. Extensive phenotypic heterogeneity has been observed among ECs of different types of blood vessels in the normal and diseased vascular wall. Although ECs with different phenotypes can share common functions, each has unique features that may dictate a fine-tuned role in vascular health and disease. Recent studies performed with single-cell technology have generated powerful information that has significantly improved our understanding of EC biology. Here, we summarize a variety of EC types, states, and phenotypes recently identified by using new, increasingly precise techniques in transcriptome analysis.